Atorvastatin reduces the risk of cardiovascular events in patients with carotid atherosclerosis: a secondary analysis of the stroke prevention by aggressive reduction in cholesterol levels (SPARCL) trial - Sillesen, Henrik; Amarenco, Pierre; Hennerici, Michael G.; Callahan, Alfred; Goldstein, Larry B.; Zivin, Justin; Messig, Michael; Welch, K. Michael (Stroke, 2008)
Background and Purpose— The Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) trial found that treatment with atorvastatin 80 mg per day reduced the risk of stroke and cardiovascular events in patients with a recent transient ischemic attack (TIA) or stroke. We hypothesized this benefit would be greatest in the subgroup of patients with carotid stenosis.Methods— The SPARCL trial randomized patients with TIA or stroke within 1 to 6 months without known coronary heart disease (CHD) and low-density lipoprotein cholesterol 100 to 190 mg/dL to treatment with atorvastatin 80 mg per day or placebo. Investigators identified subjects as having carotid stenosis not requiring revascularization at the time of randomization. Of the total SPARCL population, 1007 were documented as having carotid stenosis at baseline, 3271 did not, and the status of 453 was unknown.Results— We found no heterogeneity in the treatment effect for the SPARCL primary (fatal and nonfatal stroke) and secondary end points between the group with and without carotid stenosis. The group with carotid artery stenosis had greater benefit when all cerebro- and cardiovascular events were combined. In the group with carotid artery stenosis, treatment with atorvastatin was associated with a 33% reduction in the risk of any stroke (hazard ratio [HR] 0.67, 95% confidence interval [CI] 0.47, 0.94; P=0.02), and a 43% reduction in risk of major coronary events (HR 0.57, 95% CI 0.32, 1.00; P=0.05). Later carotid revascularization was reduced by 56% (HR 0.44, 95% CI 0.24, 0.79; P=0.006) in the group randomized to atorvastatin.Conclusion— Consistent with the overall results of the SPARCL intention to treat population, intense lipid lowering with atorvastatin reduced the risk of cerebro- and cardiovascular events in patients with and without carotid stenosis. The carotid stenosis group may have greater benefit.